The Convergence Between Cultural Psychology and Developmental Science: Acculturation as an Exemplar - Schwartz, Seth J.; Szabó, Ágnes; Meca, Alan; Ward, Colleen; Martinez, Charles R.; Cobb, Cory L.; Benet-Martínez, Verónica; Unger, Jennifer B.; Pantea, Nadina (Frontiers in Psychology, 2020)
The present article proposes an integration between cultural psychology and developmental science. Such an integration would draw on the cultural-psychology principle of culture-psyche interactions, as well as on the developmental-science principle of person↔︎context relations. Our proposed integration centers on acculturation, which is inherently both cultural and developmental. Specifically, we propose that acculturation is governed by specific transactions between the individual and the cultural context, and that different types of international migrants (e.g., legal immigrants, undocumented immigrants, refugees, asylum seekers, crisis migrants) encounter quite different culture-psyche interactions and person↔︎context relations. We outline the ways in which various acculturation-related phenomena, such as acculturation operating at macro-level versus micro-level time scales, can be viewed through cultural and developmental lenses. The article concludes with future directions in research on acculturation as an intersection of cultural and developmental processes.